Assessing Grit of Emerging Adult Diocesan Seminarians in Negros Island - Abaño, John Dave; Bedoria, Chris John (Technium Social Sciences Journal, 2023)
Grit plays a crucial role in the development of emerging adult seminarians as they undergo a rigorous process in preparation for a lifelong commitment to God and the Church. It entails a combination of persistence and passion, driving individuals to pursue their long-term goals despite facing challenges and obstacles. This study aimed to assess the extent of grit in emerging adult seminarians in four diocesan seminaries in Negros Island, particularly in terms of perseverance and consistency, and its relationship with their birth order, family structure, and income. Utilizing descriptive-correlational design, 142 emerging adult seminarians in four diocesan seminaries in negros island answered the 12-item Grit scale. The study findings indicate that the respondents, as emerging adult seminarians, possess average grit. Specifically, they demonstrate higher scores in the perseverance of effort compared to the consistency of interest. Further, the demographics such as birth order, family structure, and family income were found to have no significant correlations with grit. The results suggest that while the seminarians have the drive to endure setbacks, they may struggle with maintaining consistent choices over time. The findings also highlight that the development of grit is a personal journey, independent of factors like birth order, family structure, or family income.